COMPARATIVE PROFESSIONAL ACCOUNTANCY. - Murphy, Mary E. (The Accounting Review, 1958)
Abstract The article presents information on the comparative survey of professional organization and practice in various parts of the world. International meetings in all professional fields have become part of the normal pattern since 1945, but there is something deeper, more significant than social intercourse which draws accountants together. It is the desire to ensure the widest possible exchange of principles and procedures and to work toward the achievement of international auditing and financial reporting standards which will advance the finance and enterprise of both mature and underdeveloped countries. It is increasingly apparent that members of the U.S. profession must familiarize themselves with international profess- spinal developments as well as with international economic and political affairs. Without this specialized knowledge they cannot make a full contribution to the efficient operation of U.S. companies domiciled in foreign countries and to the encouragement of venture capital to flow overseas.